2013
DOI: 10.1097/ta.0b013e318295409d
|View full text |Cite
|
Sign up to set email alerts
|

The Burns Evaluation and Mortality Study (BEAMS)

Abstract: A highly discriminatory mortality prediction model was developed using logistic regression. Risk of death following major burns can be predicted from a combination of physiologic and burns specific parameters. Female sex is a highly significant risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 26 publications
1
16
2
Order By: Relevance
“…Wu et al showed increased plasma transfusion in burned females [26], and a paediatric study reported increased blood loss during surgery in males [11]. "Overtransfusion" of women has previously been identified in association with elective surgical procedures [28], and we have reported increased mortality in female critically ill burns patients [29]. There are gender differences in aspects of burn care, including transfusion requirements, however, at present these differences are insufficiently well understood and require further research.…”
Section: Discussionmentioning
confidence: 70%
“…Wu et al showed increased plasma transfusion in burned females [26], and a paediatric study reported increased blood loss during surgery in males [11]. "Overtransfusion" of women has previously been identified in association with elective surgical procedures [28], and we have reported increased mortality in female critically ill burns patients [29]. There are gender differences in aspects of burn care, including transfusion requirements, however, at present these differences are insufficiently well understood and require further research.…”
Section: Discussionmentioning
confidence: 70%
“…An explanation might be that females’ willingness to report problems is greater [ 47 ] or that women find it harder to live with a mutilated body. Females also reported higher levels of fatigue and higher mortality rates after burn injuries [ 47 , 48 ]. Besides, poorer outcomes in females have been shown in injury studies in general [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal function is taken into account as one of the factors affecting mortality of burned patients only in the scales generally used in Intensive Care Units based on the APACHE II system. FLAME and BEAMS scales are examples of the scales used in patients with burns [ 23 , 24 ]. None of the scales directly takes into account the strong relationship between the occurrence of renal failure and increased risk of death, which is shown in our analysis.…”
Section: Discussionmentioning
confidence: 99%